Acute Diarrhoea Management in Emergency; Influencing Antibiotic Prescribing Patterns - Islam, Mohammed Mansuri; Ahmad, Md. Parwez; Ansari, Akhtar Alam; Khatun, Tarannum; Ansari, Mohammad Ashfaque; Sarraf, Pramod Kumar (Med Phoenix, 2017)
Background: Medical students are taught the internationally accepted approach to acute diarrhoea, viz. adequate fluid and electrolyte replacement is the fundamental management of acute diarrhoea. Antibiotics should be restricted to specific indications, such as acute dysentery. Despite the well known rationale, there has been a high rate of prescription of antibiotics for acute diarrhoea presenting to Emergency. Methods: The pre and post intervention data was collected in the following way. All Emergency case records were routinely scrutinized in the Dept of Family Medicine after discharge with the exception of cases that were admitted to the wards. All cases with a discharge diagnosis fitting the clinical criteria of acute diarrhoeal syndrome: diarrhoea, gastroenteritis, dysentery and cholera were separated, analysed and recorded sequentially. Results: Initially doctors were prescribing antibiotics for 52.8% of case of non-bloody diarrhoea. In the 2nd intervention period there were few cases, but it is remarkable how few were prescribed antibiotic (20%) while the survey of prescribing habits was underway. In the 3rd intervention period when an education event took place, it was the peak of the diarrhea season. Prescribing increased somewhat to 29%. In the 4th intervention a letter was sent out to the doctors describing the results so far, and pointing out the lower prescribing by “senior doctors”. The overall changes in prescribing behaviour after the educational interventions were statistically significant. The reduction in prescribing noted when comparing intervention 1 and intervention 4, is highly significant (antibiotic p < 0.0001, anti-protozoal p<0.0001). In the 5th intervention period when appropriate prescribing was no longer actively promoted, the rate of prescribing increased again to 41.4% of cases. A similar pattern is noted for antiprotozoal prescribing. The increase in prescribing noted in the 5th period was still less than in the 1st period (antibiotic p=0.041, anti-protozoal p=0.055). The increase in prescribing from periods 4 to 5 was significant. (Antibiotics p<0.0001, anti-protozoal p = 0.012). Med Phoenix Vol.2(1) July 2017, 12-17